Performance of islamic equity and fixed-income funds during the covid-19 pandemic in Malaysia - Norhamiza Ishak; Aminah Shari; Minah Japang; Fithriah Ab Rahim (Cogent Economics & Finance, 2022)
This article discussed the impact of Covid-19 pandemic on the performance of Equity and Fixed-Income Islamic unit trusts in Malaysia. The study adopted two methods of analysis; (i) empirical analysis using conventional methodologies such as Sharpe, Treynor and Jensen in comparing the 2019 and 2020 performance of Malaysian Islamic fixed-income and Islamic equity unit trust funds, whilst run (ii) in-depth performance review on Islamic unit trusts using systematic literature review. The findings show that both the Islamic unit trust funds and fixed-income equity demonstrated fairly good performance, indicating an outperformed indicator as compared to the established benchmark during the Covid-19 pandemic. Thus, given significant positive insight to the investors would profiting from Islamic mutual or unit trust funds, by offering decent hedging for long-run investment. Second, risk-averting investors may benefit from investing in the diversified portfolios of Islamic equity funds as they have been proven to perform marginally better than conventional funds owing to better risk management.
Keywords: 330; unit trust; performance; covid-19; systematic literature review; Malaysia